Analysis of escherichia coli dan salmonella sp. in shrimp fermentation products - Sukmawati Sukmawati; Melda Yunita; Sipriyadi Sipriyadi; Erin D Noya; Henok Siboka Onim (STKIP Persada Khatulistiwa Sintang, 2022)
South Sorong, West Papua, is one of the areas that produce rebon shrimp. Rebon shrimp can be made into fermented products such as rebon shrimp paste (terasi) or acidic rebon shrimp paste (cincalok). Terasi is a food additive that functions as a seasoning or flavoring, while cincalok is a fermented food added with salt and rice. The objective of this study was to determine the contamination of E. coli and Salmonella in fermented rebon shrimp products. This study was a descriptive study by describing the presence or absence of contamination by E. coli and Salmonella sp. on rebon shrimp paste (terasi) and acidic rebon shrimp paste (cincalok). The study concluded that the samples of rebon shrimp paste (terasi) and acidic rebon shrimp paste (cincalok) in South Sorong were safe from contamination by Escherichia coli and Salmonella sp. According to the Indonesian National Standards Agency, fermented fish products with or without salt, good and suitable products for consumption are those that are negative for Salmonella, V. cholera, Escherichia coli with a limit of <3 MPN/g and Staphylococcus aureus should be <1 x103 colonies/g.